Tantangan Regulasi dan Daya Saing UMKM Blitar: Akselerasi Sertifikasi Halal untuk Pertumbuhan Ekonomi - Trisula (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2025)
This policy article discusses the low level of public awareness and understanding of the importance of halal certification, a crucial policy issue in Indonesia, impacting consumer protection and product competitiveness. This issue stems from a lack of education, procedural complexity, limited outreach, and the misperception that certification is only relevant to Muslim consumers. This policy aims to analyze and recommend policy alternatives that can effectively address these issues. Using William N. Dunn's policy alternative scoring theory, three policies are analyzed: the Integrated and Continuous Assistance Policy, the Collaboration with Communities and Religious Organizations Policy, and the Integrated Halal Certification Service Policy at the KUA Office. The analysis shows that each alternative has advantages and disadvantages. The assistance policy has high effectiveness and adequacy, but moderate efficiency. Conversely, the collaboration and integrated service policy has high efficiency and equity, but limited effectiveness. Overall, the integration of these three policies within a synergistic framework is the most ideal approach. Intensive assistance, broad collaboration, and easy access through the KUA can collectively create a strong, responsive, and equitable halal certification ecosystem. It is hoped that these recommendations can provide input for the government to formulate more comprehensive policies to increase public and business awareness and understanding of the importance of halal certification.